A novel flagellar sheath protein, FcpA, determines filament coiling, translational motility and virulence for the Leptospira spirochete. Issue 3 (24th May 2016) - Wunder, Elsio A.; Figueira, Cláudio P.; Benaroudj, Nadia; Hu, Bo; Tong, Brian A.; Trajtenberg, Felipe; Liu, Jun; Reis, Mitermayer G.; Charon, Nyles W.; Buschiazzo, Alejandro; Picardeau, Mathieu; Ko, Albert I.
Summary: Leptospira are unique among bacteria based on their helical cell morphology with hook‐shaped ends and the presence of periplasmic flagella (PF) with pronounced spontaneous supercoiling. The factors that provoke such supercoiling, as well as the role that PF coiling plays in generating the characteristic hook‐end cell morphology and motility, have not been elucidated. We have now identified an abundant protein from the pathogen L. interrogans, exposed on the PF surface, and named it Flagellar‐coiling protein A (FcpA). The gene encoding FcpA is highly conserved among Leptospira and was not found in other bacteria. fcpA ‐ mutants, obtained from clinical isolates or by allelic exchange, had relatively straight, smaller‐diameter PF, and were not able to produce translational motility. These mutants lost their ability to cause disease in the standard hamster model of leptospirosis. Complementation of fcpA restored the wild‐type morphology, motility and virulence phenotypes. In summary, we identified a novel Leptospira 36‐kDa protein, the main component of the spirochete's PF sheath, and a key determinant of the flagella's coiled structure. FcpA is essential for bacterial translational motility and to enable the spirochete to penetrate the host, traverse tissue barriers, disseminate to cause systemic infection and reach target organs. Abstract : Spirochete is a unique group of bacteria with a distinguish morphology and the presence of periplasmic flagella. Both features are essential for their ability to produce thrust even when in contact with high viscous media. In the present report, we describe a novel protein, FcpA, which is expressed exclusively in Leptospira species, confers the unique structural feature of coiled purified flagella, and is essential for the hooked‐end morphology of the bacteria. FcpA is an abundant surface expressed protein in the flagella structure, and is fundamental for the pathogen's ability to produce translational motility and virulence.